Question and Answers Forum

All Questions      Topic List

Differential Equation Questions

Previous in All Question      Next in All Question      

Previous in Differential Equation      Next in Differential Equation      

Question Number 105878 by bemath last updated on 01/Aug/20

(d^3 y/dx^3 ) + 3 (d^2 y/dx^2 ) + 2 (dy/dx) = x^2

d3ydx3+3d2ydx2+2dydx=x2

Answered by bobhans last updated on 01/Aug/20

HE : ♭^3 +3♭^2 +2♭ = 0  ♭ (♭^2 +3♭+2) = 0 → { ((♭=0)),((♭=−1)),((♭=−2)) :}  Y_h  = A+Be^(−x) +Ce^(−2x)   Particular solution. by guessing   Y_p = px^3 +qx^2 +rx  Y_p ′=3px^2 +2qx+r  Y_p ′′ = 6px+2q ; Y_p ′′′= 6p  comparing coefficient   6p+3(6px+2q)+2(3px^2 +2qx+r) = x^2   6px^2 +(18p+4q)x+6p+6q+2r = x^2    { ((6p = 1 →p=(1/6))),((18p+4q=0→q=−((9.((1/6)))/2)=−(3/4))),((r=−3p−3q=−(1/2)+(9/4)=(7/4))) :}  Y_p = (x^3 /6)−((3x^2 )/4)+((7x)/4)  General solution  Y_g = A+Be^(−x) +Ce^(−2x) +(x^3 /6)−((3x^2 )/4)+((7x)/4) ⊸

HE:3+32+2=0(2+3+2)=0{=0=1=2Yh=A+Bex+Ce2xParticularsolution.byguessingYp=px3+qx2+rxYp=3px2+2qx+rYp=6px+2q;Yp=6pcomparingcoefficient6p+3(6px+2q)+2(3px2+2qx+r)=x26px2+(18p+4q)x+6p+6q+2r=x2{6p=1p=1618p+4q=0q=9.(16)2=34r=3p3q=12+94=74Yp=x363x24+7x4GeneralsolutionYg=A+Bex+Ce2x+x363x24+7x4

Answered by mathmax by abdo last updated on 02/Aug/20

y^((3))  +3y^((2))  +2y^((1))  =x^2  let y^′  =z ⇒z^(′′)  +3z^′  +2z =x^2   h→r^2  +3r+2 =0→Δ =9−8=1 ⇒r_1 =((−3+1)/2) =−1  r_2 =((−3−1)/2) =−2 ⇒z_h =ae^(−x)  +be^(−2x)   =az_1  +bz_2   W(z_1 ,z_2 ) = determinant (((e^(−x)           e^(−2x) )),((−e^(−x)       −2e^(−2x) )))=−2e^(−3x) +e^(−3x)  =−e^(−3x)  ≠0  W_1 = determinant (((0          e^(−2x) )),((x^2          −2e^(−2x) )))=−x^2  e^(−2x)   W_2 = determinant (((e^(−x)            0)),((−e^(−x)        x^2 )))=x^2  e^(−x)   v_1 =∫ (w_1 /w) dx =−∫ ((x^2  e^(−2x) )/(−e^(−3x) ))dx =∫ x^2 e^x  dx  =x^2  e^x −∫ 2x e^x dx =x^2  e^x −2 { xe^x −∫ e^x dx}  =(x^2 −2x+2)e^x   v_2 =∫ (w_2 /w)dx  =∫  ((x^2  e^(−x) )/(−e^(−3x) ))dx =−∫ x^2  e^(2x)   =−{ (x^2 /2)e^(2x) −∫ 2x×(1/2)e^(2x)  dx} =−{(x^2 /2)e^(2x) −{ (x/2)e^(2x) −∫ (1/2)e^(2x) dx}}  =−{(x^2 /2)e^(2x) −(x/2)e^(2x)  +(1/4)e^(2x) } ={−(x^2 /2)+(x/2)−(1/4)}e^(2x)   z_p =z_1 v_(1 )  +z_2 v_2 =e^(−x) (x^2 −2x+2)e^x  +e^(−2x) (−(x^2 /2)+(x/2)−(1/4))e^(2x)   =x^2 −2x+2 −(x^2 /2) +(x/2)−(1/4) =(x^2 /2)−(3/2)x  +(7/4)  ⇒z =z_x  +z_p =ae^(−x)  +be^(−2x)  +(x^2 /2)−((3x)/2) +(7/4) =y^′  ⇒  y =∫ z(x)dx =−a e^(−x) −(b/2)e^(−2x) +(x^3 /6)−(3/4)x^2  +(7/4)x +C

y(3)+3y(2)+2y(1)=x2lety=zz+3z+2z=x2hr2+3r+2=0Δ=98=1r1=3+12=1r2=312=2zh=aex+be2x=az1+bz2W(z1,z2)=|exe2xex2e2x|=2e3x+e3x=e3x0W1=|0e2xx22e2x|=x2e2xW2=|ex0exx2|=x2exv1=w1wdx=x2e2xe3xdx=x2exdx=x2ex2xexdx=x2ex2{xexexdx}=(x22x+2)exv2=w2wdx=x2exe3xdx=x2e2x={x22e2x2x×12e2xdx}={x22e2x{x2e2x12e2xdx}}={x22e2xx2e2x+14e2x}={x22+x214}e2xzp=z1v1+z2v2=ex(x22x+2)ex+e2x(x22+x214)e2x=x22x+2x22+x214=x2232x+74z=zx+zp=aex+be2x+x223x2+74=yy=z(x)dx=aexb2e2x+x3634x2+74x+C

Terms of Service

Privacy Policy

Contact: info@tinkutara.com